The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).
The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).
The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).
The reciprocal of any number or expression is 1 divided by that number or expression. So, the reciprocal of 4x2 - 5x - 3 is simply 1 / (4x2 - 5x - 3).
-3 and 4x2 - 5x - 5 are the factors of -12x2 + 15x + 15.
-4x2 + 5x + 6 = 0 Multiply through by -1: 4x2 - 5x - 6 = 0 (I prefer the leading coefficient to be >0) 4x2 - 8x + 3x - 6 = 0 4x(x - 2) + 3(x - 2) = 0 (x - 2)(4x + 3) = 0 So x - 2 = 0 or 4x + 3 = 0 ie x = 2 or x = -3/4
4x2 -x -1 :D
y + 5x = 6 if x = {-1, 0, 1}
4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified
4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x
(4x-3)(x+2)
5x is a common factor of all terms:- 5x(x3+4x2+9)
f(x) = 8x - 4x2 - 5x - 36 = -4x2 + 3x - 36 The domain for f(x) can be the whole of the Complex field or any subset.
First you should combine equal terms. For example, 2x2 and -4x2 can be combined as -2x2. Then you can use the quadratic formula.Additonal Answer:-2x2+5x+3-4x2+22 = 0Collect like terms: -2x2+5x+25 = 0Divide al terms by -1: 2x2-5x-25 = 0Factorise: (2x+5)(x-5) = 0Solutions are: x = -5/2 or x = 5
4x2-11x-20=(x-4)(4x+5) 4x2-11x-20=4x2+ax+bx-20ab = 4*-20 = -80a+b = -11a = -16, b = 54x2-11x-20=4x2-16x+5x-204x2-16x+5x-20=4x(x-4)+5(x-4)4x(x-4)+5(x-4)=(x-4)(4x+5)Factorised, 4x2-11x-20=(x-4)(4x+5)
(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)
I suppose you mean what is an opposite reciprocal? At any rate, we should start there. The opposite reciprocal is -(1/x) so let's take the number 5. The opposite reciprocal would be -1/5. If you want two lines to be perpendicular you must take the original slope of the first line and change it to its opposite reciprocal. For example: y=5x A line perpendicular to this line would be y=-1/5x.
4x3 - 19x2 - 5x =x (4x2 - 19x - 5) =x (4x + 1) (x - 5)
Reciprocal of 3 is 1/3 Reciprocal of 35 is 1/35. Reciprocal of x is 1/x. Reciprocal of 1/3 is 3. Reciprocal of 1/x is x. It is the inverse of a number.
25x2+30x+9 25*9=225 15*15=225 15+15=3025x2+15x+15x+9[5*5xx 3*5x] [3*5x 3*3]5x(5x+3)+3(5x+3)(5x+3)(5x+3)Answer: (5x+3)2
The reciprocal of 1/3 is 3/1 = 3.